To simplify the expression \((4x^3)^3\) using the properties of integer exponents, we can apply the power of a product property which states that \((ab)^n = a^n b^n\).
- Apply the power to the constant and the variable separately:
\[ (4x^3)^3 = 4^3 (x^3)^3 \]
- Calculate \(4^3\):
\[ 4^3 = 64 \]
- Calculate \((x^3)^3\):
\[ (x^3)^3 = x^{3 \times 3} = x^9 \]
- Combine the results:
\[ (4x^3)^3 = 64x^9 \]
Now, comparing with the given options:
- Option A: \(4x^9\)
- Option B: \(64x^9\)
The correct simplified expression is Option B: \(64x^9\).
So, the answer is 2 for Option B.